We, the Elite.Storia dell'elitismo negli Stati Uniti dal 1920 al 1956 We, the Elite.History of Elitism in the United States from 1920 to 1956 - Giorgio Volpe (FedOA - Federico II University Press, 2019)
[Italiano]:Il volume affronta il problema della ricezione dell'elitismo negli Stati Uniti nel periodo tra il 1920 e il 1956, individuando i protagonisti, le fasi e i temi che la caratterizzarono. Dopo aver introdotto i principi fondamentali della teoria delle élites, la prima parte dello studio ricostruisce il dibattito che essa suscitò al di là dell'Atlantico. La seconda esamina l'originale rielaborazione americana della lezione elitista, concentrando l'analisi sulle opere degli autori più fortemente influenzati da essa: Joseph A. Schumpeter, Harold D. Lasswell, Charles W. Mills. In tal modo, lo studio mira a dimostrare come l'elitismo italiano abbia contribuito in modo significato all'elaborazione del pluralismo democratico e alla costruzione dell'egemonia politico-culturale americana nel secondo dopoguerra./[English]:This volume deals with the problem of the reception of elitism in the United States in the period between 1920 and 1956, identifying the protagonists, the phases, and the themes that characterized it. After introducing the fundamental principles of the theory of the elites, the first part of the study reconstructs the debate that it aroused beyond the Atlantic. The second part examines the original American reworking of the elitist lesson, concentrating the analysis on the works of the authors most strongly influenced by it: Joseph A. Schumpeter, Harold D. Lasswell, Charles W. Mills. In this way, the study aims to show how Italian elitism contributed in a meaningful way to the elaboration of democratic pluralism and the construction of American political-cultural hegemony in the second post-war period.